From victory to defeat : the political career of Bishop Paul of Zagreb : (1379-1394) - Petrović, Mišo (Array, 2019)
The present study analyzes the appearance of Bishop Paul of Zagreb in various sources, ranging from royal charters and other documents to later medieval chronicles. The purpose is to observe how medieval authors constructed their past and how their writings were used by subsequent historians. The first part surveys Paul’s diplomatic activities in advancing the rebellion against the Hungarian royal court within the kingdom and outside of it. The second part investigates how the institutional context of the royal court in which the sources were written shaped the way in which the memory of Paul’s participation in the rebellion was formed. As no sources which Paul himself wrote were preserved and the rebellion turned out to be unsuccessful, it was the royal narrative which influenced and defined the later image of Bishop Paul.